The Role of Parenting in Shaping Children's Personality and Character - Fajar Alfen; Yogi Nugraha; Nadya Putri Saylendra; Erwin Susanto (Sean Institute, 2024)
This research is motivated by the low discipline of children, lack of parental attention and the impact of children's discipline which is influenced by parental parenting. The purpose of this research is to know and describe scientifically and systematically about the role of parenting in shaping children's character and personality. This research uses a type of naturalistic qualitative research that describes the role of parenting in the formation of children's character and personality naturally. This research instrument is an interview and questionnaire. All data obtained is presented in narrative form. The results showed that the role of parenting in shaping children's character and personality is mostly using democratic parenting. In using a democratic parenting style, parents play an active role in providing encouragement and support so that children are always disciplined and responsible by instilling the rules that parents have set in different ways.